Solidified Floating Organic Drop Microextraction for Determination of Trace Amounts of Copper in Water Samples by Flame Atomic Absorption Spectrometry - Feng Liu, Qi; Li Dong, Yan; Jun Ma, Jing; Ci Li, Jing (Asian Journal of Chemistry, 2014)
A simple and efficient microextraction method for extraction and determination of trace amounts of copper in different water samples has been developed using solidified floating organic drop microextraction combined with flame atomic absorption spectrometry. 1-Dodecanol and NaDDTC·3H2O were used as extracting solvent and chelating agent, respectively. Under the optimized experimental conditions, a good relative standard deviation of 3.62 % at 500 μg L-1 and a detection limit of 0.3270 μg L-1 were obtained. The procedure was applied to different water samples and its accuracy was assessed through the analysis of certified reference water and recovery experiments.